2020
DOI: 10.1002/er.5852
|View full text |Cite
|
Sign up to set email alerts
|

Development of a compact simple unpressurized Watt‐level low‐temperature‐differential Stirling engine

Abstract: Despite the fast advance of modern technology, poverty is still a serious problem in many developing countries; and more than 1 billion people are having no access to electricity. For these people, even a few Watts of electricity supply for lighting can make a big difference. In this study, a simple, compact, unpressurized, Watt-level low-temperature-differential Stirling engine has been developed aiming to solve the lighting problem in developing countries. The engine in this study is compact. Yet, it is capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Stirling engine in the current study is almost identical to the engine reported in Huang and Chen [51] and Wu et al [52]. The configuration of the Stirling engine is shown in Figure 1, and the dimensions of some important geometrical parameters are listed in Table 1.…”
Section: The Present Stirling Engine the Nonpressurized γ-Typesupporting
confidence: 70%
“…Stirling engine in the current study is almost identical to the engine reported in Huang and Chen [51] and Wu et al [52]. The configuration of the Stirling engine is shown in Figure 1, and the dimensions of some important geometrical parameters are listed in Table 1.…”
Section: The Present Stirling Engine the Nonpressurized γ-Typesupporting
confidence: 70%